Wound Dehiscence after Wisdom Tooth Removal in Mandibular Mesioangular Class IB Impactions: Triangular Transposition Flap versus Envelope Flap - Rahpeyma, Amin (J Dent Res Dent Clin Dent Prospects, 2015)
Background and aims. Wound dehiscence after lower third molar surgery extends the postoperative treatment period and may cause long-standing pain. The aim of this study was to compare wound dehiscence after removal of wisdom teeth in the most prevalent mandibular impaction (mesioangular class IB) by two different soft tissue flap designs. Materials and methods. Partially-erupted mandibular third molars with mesioangular class IB impaction (Pell and Gregory classification) were selected. Split mouth technique was used to compare the two flap designs (envelope vs. triangular transposition flap—TTF). The patients were recalled one week and a month later and rechecked for dehiscence, infection, and dry socket formation. Results. There were no cases of infection in either group. However, three cases of dry socket in the envelope group and four in the TTF group were recorded. In the envelope group, dehiscence occurred in 43% of cases during the first week, with 67% of cases being a large dehiscence (diameters of more than 5 mm). Extra appointments (those requested by the patient exclusively related to the problem of the hole distal to the second molar) were scheduled in 10% of cases in the envelope group. In the TTF group, dehiscence occurred during the first week for the same impaction in 19% of cases with large dehiscence cases occurring in 65% of cases and extra appointment rate at 4.1%. Conclusion. According to theresults in the evaluated operation, TTF may prevent postoperative wound dehiscence more probably than the envelope flap.